Tindak Tutur Asertif, Direktif, Ekspresif Dalam Lirik Lagu حمود الخضر /Humood Al-Khudher/ - Hanif, Sharikhul (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This study discusses the form of illocutionary speech acts in Humūd Al Khudher's songs entitled Kun Anta (كُنْ أَنْتَ), and Salamy (سلامي). The purpose of this study was to identify the form of illocutionary speech acts in Kun Anta (كُنْ أَنْتَ) and Salamy (سلامي). The method used in this study is the listening method which is continued with the basic tapping technique then continued with the advanced technique I, namely the capable free listening technique (SBLC) and continued with the advanced technique II, namely the recording technique. An assertive speech act is a utterance intended to bind the speaker to something that happened, to the truth of the proposition that is expressed and can be judged right and wrong. the assertive type of utterance in the lyrics of Humūd Al-Khuḍer's song is to inform and affirm. A directive speech act is a speech intended by a speaker to make a speech partner do something, the directive type of utterance in the lyrics of Humūd Al-Khuḍer's song is to advise. And expressive speech acts are utterances intended to express the psychological state of the speaker specified in the propositional content, the expressive type of utterance in the lyrics of Humūd Al-Khuḍer's song is regret, respect and giving do'a.